Integration of conflict into integrative taxonomy: fitting hybridization in species delimitation of Mesocarabus (Coleoptera: Carabidae). Issue 17 (13th June 2014) - Andújar, C.; Arribas, P.; Ruiz, C.; Serrano, J.; Gómez‐Zurita, J.
Abstract In species differentiation, characters may not diverge synchronously, and there are also processes that shuffle character states in lineages descendant from a common ancestor. Species are thus expected to show some degree of incongruence among characters; therefore, taxonomic delimitation can benefit from integrative approaches and objective strategies that account for character conflict. We illustrate the potential of exploiting conflict for species delimitation in a study case of ground beetles of the subgenus Carabus (Mesocarabus), where traditional taxonomy does not accurately delimit species. The molecular phylogenies of four mitochondrial and three nuclear genes, cladistic analysis of the aedeagus, ecological niche divergence and morphometry of pronotal shape in more than 500 specimens of Mesocarabus show that these characters are not fully congruent. For these data, a three‐step operational strategy is proposed for species delimitation by (i) delineating candidate species based on the integration of incongruence among conclusive lines of evidence, (ii) corroborating candidate species with inconclusive lines of evidence and (iii) refining a final species proposal based on an integrated characterization of candidate species based on the evolutionary analysis of incongruence. This procedure provided a general understanding of the reticulate process of hybridization and introgression acting on Mesocarabus and generated the hypothesis of seven Mesocarabus species, including two putative hybrid lineages. Our work emphasizes the importance of incorporating critical analyses of character and phylogenetic conflict to infer both the evolutionary history and species boundaries through an integrative taxonomic approach.